Hydrothermal synthesis of zinc oxide (ZnO) microparticle - Pookmanee P. (2014)
Zinc oxide (ZnO) microparticle was synthesized by hydrothermal route using zinc acetate and ammonium hydroxide as the starting precursors in the mole ratio of 1:6. The final mixture solution was adjust with pH of 9 and treated in PTFE-line autoclave at 100 °C for 2, 4 and 6 h. The precipitate was washed with deionized water until the final pH solution of 7 and then dried at 100 °C for 4h. The phase structure was examined by X-ray diffraction (XRD). A single phase hexagonal structure was obtained without calcination step. Microstructure was investigated by scanning electron microscopy (SEM). The particle size of ZnO was in the range of 0.15-1.5 μm with irregular in shape. The chemical composition was identified by energy dispersive X-ray spectroscopy (EDXS). The elemental composition of ZnO showed the characteristic X-ray energy value as follows: zinc of Lα = 1.012 keV, Kα = 8.630 keV and Kβ = 9.570 keV and oxygen of Kα = 0.525 keV, respectively. © 2008 Trans Tech Publications, Switzerland.